Authentic Englishes.nrw – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, Stefan; Fiege, Amanda Sophie; Mindt, Ilka (Selected Papers from the 2021 Conference of the German Association for the Study of English)

Introduction: English Linguistics, Learners and the Classroom - Hahn, Charlotte Anna; Mindt, Ilka (Anglistik)
Keywords: General Medicine

‘Authentic Englishes.nrw’ – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, S.; Fiege, Amanda Sophie; Mindt, Ilka (Anglistik)
Keywords: General Medicine

"There". Die Verwendung von "there" im authentischen Englisch, im Englisch von Lernenden und in Schulbüchern - Mindt, Ilka (Sprachwissenschaft und Fremdsprachendidaktik: Konstruktionen und Konstruktionslernen)

Student engagement in digitalen Lehr-Lern-Szenarien - Mindt, Ilka; Rebekka, Schmidt (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre.)

Student engagement in digitalen Lehr-Lern-Szenarien - Schmidt, Rebekka; Mindt, Ilka (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre)
In diesem Beitrag wird das Konzept des student engagement mit den drei Dimensionen Verhalten, Emotion und Kognition skizziert und in Bezug auf die unterstützenden Faktoren für Lehre auf Distanz in digitalen Lehr-Lernsettings untersucht. Ein Abgleich der theoretischen Grundlagen mit Forschungsergebnissen verschiedener Studien zum Onlinesemester 2020 sowie eine Konkretisierung durch Evaluationen aus Seminaren der englischen Sprachwissenschaft und der Kunstdidaktik gibt Aufschluss darüber, wie ein geeignetes how to engage auch in digitalen Lehr-Lernsettings gelingen kann. Darüber hinaus lassen die Ausführungen erkennen, dass die unterstützenden Faktoren häufig in ähnlich priorisiert werden. Daraus ergibt sich eine Reihenfolge mit dem unterstützenden Umfeld an erster, aktivem und kollaborativem Lernen an zweiter, Erleben von Kompetenz an dritter und akademischer Herausforderung an vierter Stelle. Die Ergebnisse können damit einen Weg aufzeigen, wie auch in ungewohnten Lehr-Lernsettings sukzessive ein geeignetes how to engage entwickelt werden kann, um student engagement zu fördern.

Student engagement in digitalen Lehr-Lern-Szenarien. Zwei Fachdisziplinen berichten - Schmidt, Rebekka; Mindt, Ilka (Hochschule auf Abstand)

Einleitung - Meister, Dorothee; Mindt, Ilka (Mobile Medien im Schulkontext)

Digitale Elemente im Englischunterricht - Mindt, Ilka; Kaymak, Yasemin (Mobile Medien im Schulkontext)

Viele Wege führen nach Rom - Möglichkeiten und Modelle des Inverted-Classroom-Modells aus interdisziplinärer Sicht - Schmidt, Rebekka; Dietrich, Nico; Mindt, Ilka (Digitale Innovationen und Kompetenzen in der Lehramtsausbildung)

Mit digitalen Arbeitsformen das Lernen bereichern: zur Gestaltung sinnstiftender Präsenzphasen mit dem Inverted-Classroom-Modell - Mindt, Ilka; Schmidt, Rebekka; Beißwenger, Michael; Dietrich, Nico (Digitale Innovationen und Kompetenzen in der Lehramtsausbildung)

Student engagement im Inverted Classrom - Mindt, Ilka; Schmidt, Rebekka (Tagungsband zur Tagung Inverted Classroom and beyond 2020)

Kristin Bech and Ruth Möhlig-Falke, eds. Grammar – Discourse – Context: Grammar and Usage in Language Variation and Change. Berlin and Boston, MA: De Gruyter, 2019 - Mindt, Ilka

Student engagement im Inverted Classrom - Schmidt, Rebekka; Mindt, Ilka (Tagungsband zur Tagung Inverted Classroom and beyond)

Bridging - Fremdsprache und Fachwissenschaft. Digital Learning Map - Mindt, Ilka

"Digital Humanitites: The Role of the Digital in English Philology". Sprachwissenschaftliche Sektion beim Anglistentag 2017 in Regensburg - Mindt, Ilka; Bartsch, Sabine (Anglistentag 2017 Regensburg. Proceedings)

Section I: Digital Humanities: The Role of the Digital in English Philology - Bartsch, Sabine; Mindt, Ilka (Anglistentag 2017 Regensburg. Proceedings)

Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka

Proceedings of the BHQFHE projects. Basis, Analysis, Development, Impact and Prosepcts of the BHQFHE Tempus Project

Chosen - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik)

Analyzing Corpus Data from Within - Mindt, Ilka (Anglistik. International Journal of English Studies)

An interview with Joybrato Mukherjee, the Chair oft he ICAME Board - Kytö, Merja; Stenström, Anna-Brita; Mindt, Ilka (ICAME Journal 40)

The diachronic development of 'COME TO V' - Mindt, Ilka (Silesian Studies in English 2015)

Anglistentag 2015 Paderborn: Proceedings

Gesprochene Korpora des Englischen und ihre Anwendung in der Grammatikforschung - Mindt, Ilka (Grundlagen einer sprachwissenschaftlichen Quellenkunde)

Talking like a book. Investigating colloquialization as a change in written English - Mindt, Ilka (Oralité(s) et écriture(s))

Change in Contemporary English. A Grammatical Study - Mindt, Ilka; Leech, Geoffrey; Hundt, Marianne; Mair, Christian; Smith, Nicholas (Archiv für das Studium der neueren Sprachen und Literaturen 164: 249: 2)

Adjective complementation by that-clauses: An empirical study - Mindt, Ilka

Corpus Linguistics and the Description of English - Mindt, Ilka; Lindquist, Hans (ICAME Journal 35)

Anglistische Korpuslinguistik. Eine Einführung. Grundlagen der Anglistik und Amerikanistik 33 - Mindt, Ilka; Mukherjee, Joybrato (Anglistik. International Journal of English Studies, 22, 1)

Beiträge der Sektion I "'Spoken' English through the Centuries." Sprachwissenschaftliche Sektion beim Anglistentag 2009 in Klagenfurt. - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Spoken English through the centuries: Introduction - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Methoden der Korpuslinguistik: Der korpus-basierte und der korpus-geleitete Ansatz - Mindt, Ilka (Kompendium Korpuslinguistik. Eine Bestandsaufnahme aus deutsch-tschechischer Perspektive)

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Appropriateness in Discourse: The adjectives surprised and surprising in monologue and dialogue - Mindt, Ilka (Journal of Pragmatics)

Progressives, Patterns, Pedagogy. A corpus-driven approach to English progressive forms, functions, contexts and diadactic - Mindt, Ilka; Römer, Ute (Anglistik. International Journal of English Studies, 19, 2)

Corpus Linguistics 25 Years on. (Language and Computers: Studies in Practical Linguistics 62) - Mindt, Ilka; Facchinetti, Roberta (ICAME Journal, Computers in English Linguistics, 2008)

The valency of experiential and evaluative adjectives - Mindt, Ilka (Valency. Theoretical, Descriptive and Cognitive Issues)

Learner English: Ein Überblick über vorhandene Korpora und mögliche Forschungsansätze - Mindt, Ilka (Korpuslinguistik Deutsch: synchron – diachron – kontrastiv. Würzburger Kolloquium 2003)

Corpora in Applied Linguistics - Mindt, Ilka; Hunston, Susan (ICAME Journal 29, Computers in English Linguistics)

A Student's Introduction to English Grammar - Mindt, Ilka; Huddleston, Rodney; Pullum, Geoffrey K. (Zeitschrift für Anglistik und Amerikanisitk. A Quarterly of Language, Literature and Culture. Heft 2, 2)

Lexikalische Dynamik: Kognitiv-linguistische Untersuchungen am englischen Computerwortschatz - Mindt, Ilka; Bründl, Monika Elisabeth (Anglistik. Mitteilungen des Deutschen Anglistenverbandes)

Is I think a Discourse Marker - Mindt, Ilka (Anglistentag 2002 Bayreuth. Proceedings of the Conference of the German Association of University Teachers of English, Volume XXIV)

Tagungsbericht über das Internationale Kolloquium Korpuslinguistik Deutsch: synchron – diachron – kontrastiv (klde 2003) - Mindt, Ilka (Zeitschrift für Deutsche Philologie 122)

Form and function of parasyntactic presentation structures. A corpus-based study of talk units in spoken English - Mindt, Ilka; Mukherjee, Joybrato (ICAME Journal, 27, Computers in English Linguistics)

Functions of intonation in sentences and texts - Mindt, Ilka (New Frontiers of Corpus Research. Papers from the Twenty First International Conference on English Language Research on Computerized Corpora)

Emerging English Modals: A Corpus-Based Study of Grammaticalization - Mindt, Ilka; Krug, Manfred (Journal of English Linguistics, Volume 30, Number 3)

Intonation im Lancaster/IBM Spoken English Corpus. Falls und fall-rises, Sprecherwechsel, paratones, declination - Mindt, Ilka

Longman Idioms Dictionary - Mindt, Ilka (Anglistik. Mitteilungen des Deutschen Anglistenverbandes)

New Zealand English Grammar Fact or Fiction? A corpus-based study in morphosyntactic variation - Mindt, Ilka; Hundt, Marianne (Anglistik: Mitteilungen des Deutschen Anglistenverbandes)

Prosodic Cues at Speaker Turns - Mindt, Ilka (Corpus Linguistics and Linguistic Theory. Papers from the Twentieth International Conference on English Language Research on Computerized Corpora (ICAME 20))